2010
DOI: 10.1016/j.jpainsymman.2009.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Computer-Based Quality-of-Life Monitoring in Brain Tumor Outpatients in Routine Clinical Practice

Abstract: The software-generated graphic QOL profiles were found to be an important tool for screening patients for clinically relevant problems. Thus, computer-based QOL monitoring can contribute to an optimization of treatment (e.g., symptom management, psychosocial interventions) and facilitate data collection for research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 24 publications
3
84
1
1
Order By: Relevance
“…Thus, routine screening for these and other symptom problems using Patient-Reported Outcomes Measures (PROMs) has emerged as a standard of care in many cancer organizations. [20][21][22][23] To date, most PROMs have been implemented as a rapid screening maneuver using brief, single dimension severity scales such as the Distress Thermometer or the Edmonton Symptom Assessment System (ESAS). 24,25 Unidimensional measures do not capture the multidimensional nature of these problems and thus may lack precision in estimating severity and detecting responsiveness to change in individuals.…”
Section: Accepted Articlementioning
confidence: 99%
“…Thus, routine screening for these and other symptom problems using Patient-Reported Outcomes Measures (PROMs) has emerged as a standard of care in many cancer organizations. [20][21][22][23] To date, most PROMs have been implemented as a rapid screening maneuver using brief, single dimension severity scales such as the Distress Thermometer or the Edmonton Symptom Assessment System (ESAS). 24,25 Unidimensional measures do not capture the multidimensional nature of these problems and thus may lack precision in estimating severity and detecting responsiveness to change in individuals.…”
Section: Accepted Articlementioning
confidence: 99%
“…The nurses in the current study also mentioned that these issues were difficult to discuss with the patients. Training of the staff's communications skills is highlighted as a crucial point in interpreting feedback from the patients through electronic systems [42,43]. Heaven et al point out that clinical supervision is essential to effectively transfer skills learned during communication training into clinical practice [44].…”
Section: Compatibilitymentioning
confidence: 99%
“…Frequently discussed problems in assessing electronic PRO data include patient age and related computer literacy [10,[21][22][23][24], as well as the additional time and burden for the patient and healthcare institutions in supplying electronic devices and giving instruction on their use [22,[25][26][27][28][29]. However, this study showed that age was not a factor.…”
Section: Discussionmentioning
confidence: 80%
“…Electronic questionnaire administration is not yet common in the orthopedic field, but more experience and relevant literature are available in the field of oncology where data collection was introduced in the 1990s [23,26,27,[30][31][32]. Study populations in oncology are often comparable to arthroplasty populations in terms of age and computer literacy.…”
Section: Discussionmentioning
confidence: 99%